THE POSITION OF THE UZBEK LANGUAGE AS THE STATE LANGUAGE - Azizova, Saodat Tursunniyozovna (Educational Research in Universal Sciences, 2023)
The article describes the value and prestige of the Uzbek language, which is our state language, as the national pride, pride and face of our people, as well as its importance in the development of education.